Η σημασία των παραλιών της Μικράς Ασίας στην παραγωγή και τη διακίνηση του υστερορωμαϊκού/πρωτοβυζαντινού αμφορέα 1 (=LRA 1): Αρχαιολογικές μαρτυρίες και επιγραφικές συμβολές - Διαμαντή Χαρίλεια (Δελτίο Κέντρου Μικρασιατικών Σπουδών, 2008)
Within the new geopolitical environment which is shaped for the Byzantine Empire during the Protobyzantine period, Constantinople as a New Rome, constitutes the administrative as well as the financial centre of the Empire. In Constantinople end up basic financial routes, that concern not only the exterior trade with the East but also the internal commerce of the Mediterranean which extended from Asia Minor to France, Spain and Great Britain and from North Africa to Constantinople. As a result, the coastline of Asia Minor gets also higher geographical importance as it is situated among the naval commercial roads uniting the new capital with the eastern regions and the West Mediterranean. The spreading and the common use of the same type of amphorae all over the Mediterranean can constitute a means of documentation for these commercial roads, of the financial relations between the production centres of these vases and the centres of their import. In this text an effort is made for a combined presentation of the archaeological and historical information which sets off the role of the Asia Minor coastline in the naval commerce of wine during the late Roman / Protobyzantine era. We examine the example of Kilikia region as a production centre and maybe even more as the place of origin of the Late Roman Amphorae 1.